Maritime Defense Diplomacy Strategy Cultural Approach of Gunung Padang Site Facing Problems in the North Natuna Sea - Prakoso, Lukman Yudho; Alman, Fariel Zulfikar; Alman, Gabriel Choirul; Rianto, Rianto; Patmi, Sri; Habibie, Sri Yaumil; Soemantri, Asep Iwa; Prasetyo, Heru (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This study analyzes the maritime defense diplomacy strategy with the cultural approach of the Gunung Padang Site in dealing with problems in the North Natuna Sea. The cultural approach was chosen as the basis for the strategy to assert Indonesia's sovereignty over its maritime territory which is threatened by claims from other countries. With a focus on the Gunung Padang Site as a symbol of Indonesia's rich cultural heritage, this study explores the potential for cultural diplomacy in strengthening Indonesia's claim to the North Natuna Sea. The research method used is qualitative descriptive with a literature study approach, collecting data from primary and secondary sources related to history, culture, and maritime diplomacy. The results of the analysis show that the integration of culture in maritime defense diplomacy provides a stronger and more convincing dimension in voicing Indonesia's national interests. The recommendations produced include strengthening cultural diplomacy, developing communication infrastructure and diplomatic capabilities, more intensive international collaboration, and increasing research and analysis on the relationship between culture and maritime interests. It is hoped that the results of this study can provide a positive contribution in efforts to maintain Indonesia's maritime sovereignty and security in the North Natuna Sea.